Pericolosità sociale e malattia mentale. Introduzione - Fargnoli, Domenico (Il sogno della farfalla, 2019)
This article introduces a monographic issue which through the contribution of psychiatrists, magistrates and journalists aims at proposing a new perspective on the social danger question both on a legal and nosographic-therapeutic aspect.